The influence of fintech on the non-performing loan rate of commercial banks evidence from China - Huaqiuhao Wu (2022)
This dissertation explore the impact of the development of fintech technology on the non-performing loan rate through statistical analysis of the data of several Chinese commercial banks during the period of 2011-2019. This document employs the multilevel regression analysis, and the data collected include listed commercial banks, state-owned banks, and unlisted commercial banks. At the same time, macroeconomic variables are also added as control variables. The results of the random effects model show that the development of fintech technology has slightly increased the non-performing loan rate of listed commercial banks, while the Fintech index has no statistically significant impact on unlisted commercial banks. The results are also subject to robustness checks.